Reconstruction of Trade Secret Clauses in F&B Franchises: Mitigating Loss Aversion through a Risk Allocation Approach - Sinaga, Irene Puteri Alfani Sofia; Mulyono, Fadhel Koto Bida (SIGn Jurnal Hukum, 2025)
The Food and Beverage (F&B) franchise sector in Indonesia faces a juridical paradox. Aggressive trade secret protection efforts precisely result in systemic unenforceability in court. This study aims to dissect the root causes of evidentiary failures regarding the “reasonable steps” element in franchise disputes and to formulate a proportional, enforceable operational clause model. Through a normative juridical method with an interdisciplinary approach, this study integrates Legal Certainty Theory, Prospect Theory from behavioral economics, and Risk Allocation Theory as diagnostic, evaluative, and prescriptive analysis tools. Research findings reveal that ambiguous and lop-sided protection clauses are not merely administrative errors. They constitute a manifestation of the franchisor’s irrational loss-aversion bias. Excessive fear of losing vital assets drives the creation of excessive contracts that violate the principle of good faith and fail to fulfill the objective requirements of an agreement. This condition fatally undermines the validity of digital evidence under Law Number 11 of 2008. As a prescriptive solution, this research recommends a fundamental reconstruction of contractual instruments, shifting from the loss-aversion paradigm to an equitable Risk Allocation Theory. The proposed operational clause model includes a limiting definition of a secret object, layered confidentiality obligations, a notice-and-cure mechanism, and reasonable time and territorial restrictions on the non-competition clause. This reconstruction aims to guarantee practical legal certainty and the sustainability of the national franchise business ecosystem.